PENGARUH KESADARAN WAJIB PAJAK, KEWAJIBAN MORAL, TINGKAT PENGHASILAN, PELAYANAN FISKUS, DAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: Studi Empiris di UPTD Pelayanan Pajak dan Retribusi Daerah Provinsi Bali di Kota Denpasar - Dea Nirmala Sari; Ketut Yudana Adi (Journal Research of Accounting, 2023)
Taxpayer compliance can be interpreted as the attitude or behavior of a taxpayer in carrying out his tax obligations and enjoying his tax rights in accordance with applicable laws and regulations. The higher the level of taxpayer compliance in paying tax obligations, the tax revenue will increase. This study aims to empirically examine the effect of taxpayer awareness, moral obligation, level of income, tax authorities and sanctions on the level of motor vehicle tax compliance. This research was conducted at the Denpasar City SAMSAT Office. The type of data used is quantitative data, this research data is in the form of primary data and data collection is done by distributing questionnaires to motor vehicle taxpayers. The total population in this study is 1,470,570 motor vehicle taxpayers. Determination of the sample using accidental sampling technique with the number of samples used as many as 100 taxpayers who are determined using the solvency formula. The data analysis technique used is multiple linear regression. The results of this study are able to show that there is support from the use of the theory of planned behavior and the theory of compliance with the factors that influence the perception of taxpayers in taxpayer compliance. The results of the study show that taxpayer awareness, moral obligation, level of income, tax authorities and sanki services have a positive and significant effect on motor vehicle taxpayer compliance at the SAMSAT Office of Denpasar City.